Antimicrobial activity of marine fungi isolated from the Son Tra peninsula, Da Nang, Vietnam - Trinh, Phan Thi Hoai; Duy Ngoc, Ngo Thi; Dieu Trang, Vo Thi; Phong, Le Quoc; Tien, Phi Quyet; Ly, Bui Minh; Thanh Van, Tran Thi (Academia Journal of Biology, 2018)
Marine fungi have become an important source of bioactive natural products. The present study was concerned with the screening of antimicrobial activity from 73 fungal strains isolated from various marine habitats collected from five different localities at the Son Tra Peninsula, Da Nang, Vietnam. For the first step of screening, ethyl acetate extract of each fungal isolate was prepared and their antimicrobial activity against the human microbial pathogens was investigated using the disc diffusion method. The panel of human microbial pathogens used were Bacillus cereus ATCC 11778, Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853, Listeria monocytogenes ATCC 19111, Streptococcus faecalis ATCC 19433 and Candida albicans ATCC 10231. Among 73 fungal isolates, 29 exhibited antimicrobial activity against at least two tested pathogens. The proportion of the fungal isolates having anti-microbial activity against B. cereus, S. faecalis, L. monocytogenes, S. aureus, E. coli, C. albicans and P. aeruginosa were 42, 33, 31, 22, 7, 5 and 3%, respectively. Further investigations to isolate and characterize the anti-microbial components in the extracts are needed. Citation: Phan Thi Hoai Trinh, Ngo Thi Duy Ngoc, Vo Thi Dieu Trang, Le Quoc Phong, Phi Quyet Tien, Bui Minh Ly, Tran Thi Thanh Van, 2017. Antimicrobial activity of marine fungi isolated from the Son Tra peninsula, Da Nang, Vietnam. Tap chi Sinh hoc, 39(4): 457-462. DOI: 10.15625/0866-7160/v39n4.8889. *Corresponding author: phanhoaitrinh84@gmail.com Received 20 November 2016, accepted 12 August 2017